Use of 1‐bit digital‐to‐analogue converters in massive MIMO systems. Issue 9 (4th April 2016) - Guerreiro, J.; Dinis, R.; Montezuma, P.
Abstract : Massive multiple‐input multiple‐output (MIMO) systems are being proposed for next generation broadband wireless systems. However, as the complexity of implementation grows with the number of antenna elements, their feasibility is a challenging task. Consider very low complexity, 1‐bit digital‐to‐analogue converters (DACs) for the downlink of massive MIMO systems. The impact of the resultant severe non‐linear distortion effects is analysed when a low‐complexity maximum ratio transmission technique is employed for user separation. The non‐linear distortion levels decrease with the number of transmit antennas allowing good performance, even with 1‐bit DACs are shown.